Differential pH‐sensitive sensor with DC electrode‐offset compensation. Issue 4 (1st February 2017) - Lee, K.H.; Lee, D.; Yoon, J.; Kwon, O.; Lee, J.
Abstract : A pH‐sensitive sensor with a differential mode was developed to detect surface charges accumulated on the ion‐sensitive layer. The device accurately monitors the relative pH value using the modified instrumentation amplifier with the DC electrode‐offset compensation. The readout voltage is digitalised with the current‐starved ring oscillator. The sensor achieves the DC offset compensation of 22.5 dB and the oscillating pH sensitivity of 1.3 MHz/pH. The feasibility of the sensor is demonstrated to monitor the hydrogen ion concentration comparing the oscillation frequency at differential mode with that at single mode.